17 kunstenaars uit Bremen. - Henderickx, Sjef; Opper, Dieter; Paalman, Hans (Schiedam : Stedelijk Museum Schiedam, 1981)
Baumgärtel, Christa ; Greune, Karl Heinrich ; Hartmann, Thomas ; Kraft, Bodo ; Michael, Wolfgang ; Müller, Horst ; Niebuhr, Louis ; Otto, Waldemar ; Recker, Thomas ; Schmiedekampf, Jürgen ; Schwontkowski, Norbert ; Streich, Helmut ; Splettstösser, Peter Jörg ; Stuzmann, Hermann ; Tollmann, Günter ; Volker, Otto ; Wienbeck, Rolf-Andreas
biog., ind. tent. gr. tent. per kunstenaar
Nederlands
17 kunstenaars uit Bremen, Stedelijk Museum Schiedam, 21 maart t/m 3 mei 1981
boek